Comparing Audience Perceptions of Characters in Subtitled Film: Validating a Strategy for Assessing Equivalence of Character Voice - Nettelbeck, Hugh Wilson (Journal of Audiovisual Translation, 2020)
Understanding of key character attributes in foreign film may be reduced when perception is dependent on subtitles. This research aimed to validate a reception-based method for empirically measuring functional equivalence of character voice in subtitled film. Participants watched a Japanese film excerpt, with or without English subtitles, and rated their impressions of the central character (Takuji) on 16 character descriptors (8 antonym pairs), identified by the author as important for understanding Takuji. Perceptions of Takuji’s personality were compared between Japanese and English speakers in two studies (Study 1, N = 49, 28 Japanese, 21 English; Study 2, N = 53, 23 Japanese, 30 English). Both studies involved assessment of Takuji by Japanese speakers (no subtitles) and English speakers (English subtitles). Study 2 attempted to improve inter-item reliability and equivalence between languages by using more direct antonyms and longer descriptors than Study 1. Results from both studies established significant differences in character perceptions between Japanese and English viewers and confirmed the reliability of Japanese intracultural perceptions. Consistency in the loss of character voice between language groups in both studies confirmed that this approach to measuring character voice has strong potential for assessing subtitling approaches that aim to address functional equivalence in character perception.